2022
DOI: 10.1021/acs.biochem.2c00524
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of the Electron Transfer Pathways in the Homodimeric Photosynthetic Reaction Center

Abstract: Photosynthetic reaction centers from a green sulfur bacterium (GsbRC), the PscA/PscA proteins, and photosystem I (PSI), PsaA/PsaB proteins, share structural similarities. Here, we report the redox potential (E m ) values of GsbRC by solving the linear Poisson−Boltzmann equation and considering the protonation states of all titratable sites in the entire GsbRC protein and identify the factors that shift the E m values with respect to PSI. The E m values for oneelectron reduction of the accessory (A −1 ) and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 50 publications
0
27
2
Order By: Relevance
“…1,33 The uptake of 0.4 H + by PscA-Asp634 was also observed in response to F X − formation in GsbRC, which suggests that its protonation state is coupled with the redox state of F X in GsbRC. 15 However, the present study shows that no proton uptake is observed in response to the formation of A 0…”
Section: ■ Methodscontrasting
confidence: 65%
See 4 more Smart Citations
“…1,33 The uptake of 0.4 H + by PscA-Asp634 was also observed in response to F X − formation in GsbRC, which suggests that its protonation state is coupled with the redox state of F X in GsbRC. 15 However, the present study shows that no proton uptake is observed in response to the formation of A 0…”
Section: ■ Methodscontrasting
confidence: 65%
“…They are conserved as PscA-Arg502 and PscA-Arg638 in GsbRC (Figure ). In GsbRC, PscA-Arg502 also increases E m (A 0 /GsbRC) most significantly . PscA-Arg638 not only serves as a binding site of a phosphatidylglycerol molecule but also increases E m (A 0 /GsbRC) with respect to E m (A 0 /PSI) .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations